The egg and I - MacDonald, Betty Bard. (New York : Pocket Books, 1949)
The author relates the joys and frustrations of life on a poultry farm in the mountains of Washington.
Keywords: MacDonald, Betty Bard; Authors, American -- 20th century -- Biography; Farm life -- Washington (State); Farm life -- Wit and humor; Farmers; Washington (State) -- Biography